The role of English in the process of transformation of public consciousness - Baturin, V.S.; Abramovich, Ye.A. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article is devoted to the issues connected with the need to understand the importance and necessity of the transformation of public consciousness at the present stage of development of Kazakhstani society. This will in many respects help to resolve the problems connected with the country's desire to enter the top thirty of the most developed countries of the world. Nowadays, the most important condition for the formation of a person's competitiveness is not only his professional knowledge and skills, but also the knowledge of foreign languages. The solution of this task in Kazakhstan is largely connected with the approved policy of introducing trilingualism, which implies mastering English along with Kazakh and Russian. Today, it is the English language that is called upon to play a significant role on the way of Kazakhstanis entering the modern world of business, innovation and technology. The article emphasizes that the mastering English opens up ample opportunities for students to get education in different countries of the world, for the exchange of specialists in various fields of activity. At the same time, this significantly increases the level of requirements for mastering this language. A special role in overcoming the difficulties along this path, in the authors’ opinion, is called upon the transition of Kazakh to the Latin alphabet. Since Latin graphics are even more common than English. At the same time, this will also simplify to a certain extent the very process of mastering English. The transition of Kazakhstan to the path of mastering poly-lingualism by its citizens is its adequate response to the objective requirement of the course of modern globalization processes. Simultaneously, this will help the republic to contribute to the development of the treasury of world's human culture.
Қоғамдық сананы өзгерту үрдісінде ағылшын тілінің рөлі
Роль английского языка в процессе трансформации общественного сознания
Keywords: English language; modernization; transformation; culture of thinking; human capital; competitiveness.